AB0814 SUSTAINED IMPROVEMENTS IN PHYSICAL FUNCTION, QUALITY OF LIFE, AND WORK PRODUCTIVITY WITH IXEKIZUMAB IN PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS AND PREVIOUS INADEQUATE RESPONSE TO TUMOUR NECROSIS FACTOR-INHIBITORS: 3-YEAR RESULTS FROM SPIRIT-P2 TRIAL. (2nd June 2020) - Orbai, A. M.; Gratacos-Masmitja, J.; Dokoupilova, E.; Combe, B.; Constantin, A.; Gellett, A. M.; Sprabery, A. T.; Birt, J.; Geneus, V.; Nash, P.
Abstract : Background: Ixekizumab (IXE), a high-affinity monoclonal antibody that selectively targets IL-17A, has shown improvements compared to placebo (PBO) not only in disease activity but also in various patient-reported outcomes (PROs) assessing physical function, quality of life (QoL), and work productivity in PsA patients treated for 24 weeks and sustained up to 52 weeks. 1, 2 Objectives: To report the effects of treatment with IXE on these PROs after up to 3 years of treatment. Methods: In SPIRIT-P2 (NCT02349295 ), a Phase 3 trial, 363 adult patients with active PsA and prior inadequate response or intolerance to 1 or 2 TNF inhibitors (TNFis) were randomized 1:1:1 to IXE 80 mg every 4 weeks (IXEQ4W; N=122) or every 2 weeks (IXEQ2W; N=123), or PBO (N=118) in the double-blind treatment period (Weeks 0-24). Both IXE regimens had a starting dose of 160 mg. Results are reported from a subset of the intent-to-treat population who were randomized to IXE at baseline (Week 0). The following PROs were assessed during Weeks 0-156: HAQ-DI (minimally clinically important difference [MCID] an improvement ≥0.35), medical outcomes survey Short Form-36 (SF-36) Physical and Mental Component Summary (PCS and MCS), European Quality of Life 5 Dimensions Visual Analog Scale (EQ-5D VAS), and Work Productivity and Activity Impairment Questionnaire-Specific Health Problem (WPAI-SHP; absenteeism, presenteeism, work productivity, and activity impairment). Missing values were imputed by observed analysis and modified baseline observation carried forward (mBOCF) for continuous data or by modified non-responder imputation (mNRI) for categorical data. Results: Mean baseline scores for SF-36 (PCS and MCS), EQ-5D VAS, and WPAI-SHP (Figure 1 ) and HAQ-DI (mean [SD]: IXEQ4W=1.2 [0.6]; IXEQ2W=1.2 [0.6]), indicated impaired physical function and QoL. The percentage of patients of who completed 156 weeks of the study in IXEQ4W and IXEQ2W arms were 57.4% (n=70) and 44.7% (n=55), respectively. Patients receiving IXE treatment up to 3 years reported sustained improvements in SF-36 (PCS and MCS), EQ-5D VAS, and WPAI-SHP (presenteeism, work productivity, and activity impairment) (Figure 1 ). Observed HAQ-DI mean change from baseline in IXEQ4W: -0.46 (0.62) and IXEQ2W: -0.48 (0.55). The percentage of IXE treated patients achieving MCID for HAQ-DI (improvement ≥0.35) was sustained at 3 years (Figure 2 ). Conclusion: Improvements in PROs, measuring physical and mental function, quality of life, and work productivity are maintained up to 3 years with IXE treatment in patients with active PsA who have had an inadequate response or intolerance to 1 or 2 TNFis. References: [1]Nash P, et al. Lancet. 2017;389(10086):2317-2327. [2]Genovese MC, et al. Rheumatology (Oxford). 2018;57(11):2001-2011. Disclosure of Interests: Ana-Maria Orbai Grant/research support from: Abbvie, Eli Lilly and Company, Celgene, Novartis, Janssen, Horizon, Consultant of: Eli Lilly; Janssen; Novartis; Pfizer; UCB. Ana-Maria Orbai was a private consultant or advisor for Sun Pharmaceutical Industries, Inc, not in her capacity as a Johns Hopkins faculty member and was not compensated for this service., Jordi Gratacos-Masmitja Grant/research support from: a grant from Pfizzer to study implementation of multidisciplinary units to manage PSA in SPAIN, Consultant of: Pfizzer, MSD, ABBVIE, Janssen, Amgen, BMS, Novartis, Lilly, Speakers bureau: Pfizzer, MSD, ABBVIE, Janssen, Amgen, BMS, Novartis, Lilly, Eva Dokoupilova Grant/research support from: Eli Lilly and Abbvie, Bernard Combe Grant/research support from: Novartis, Pfizer, Roche-Chugai, Consultant of: AbbVie; Gilead Sciences, Inc.; Janssen; Eli Lilly and Company; Pfizer; Roche-Chugai; Sanofi, Speakers bureau: Bristol-Myers Squibb; Gilead Sciences, Inc.; Eli Lilly and Company; Merck Sharp & Dohme; Pfizer; Roche-Chugai; UCB, Arnaud Constantin Grant/research support from: Study was sponsored by Sanofi Genzyme, Consultant of: Consulting fees from Abbvie, BMS, Celgene, Gilead, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, Amanda M. Gellett Shareholder of: Eli Lilly and company, Employee of: Eli Lilly and company, Aubrey Trevelin Sprabery Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Julie Birt Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Vladimir Geneus Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB